Flood Risk of Metro Manila Barangays: A GIS Based Risk Assessment Using Multi-Criteria Techniques - Pornasdoro, Karlo P.; Silva, Liz C.; Munárriz, Maria Lourdes T.; Estepa, Beau A.; Capaque, Curtis A. (Journal in Urban and Regional Planning; Vol 1 No 1 (2014): Journal in Urban and Regional Planning, 2014)
This study examined the flood prone areas within Metro Manila to find out their degrees of disaster risk. More specifically, the study considered the population densities of Metro Manila barangays, the smallest political units of the country, the gender and age population, the structural materials and the recorded depths of flooding. Geographic Information System (GIS) using multi-criteria techniques was the tool of analysis of the study. Projecting the population density of each barangay, the children, elderly and women populations to 2020 and 2030 and simultaneously examining the recorded depths of its flood waters and existing structural materials, the study identified the barangays that will be at high risk by 2020 and 2030. Although the study is limited to population data and physical characteristics of barangays, the findings may be useful to urban and regional planners and government agencies involved in disaster risk reduction and mitigation management. The study can be integrated in future development plans of specific areas and be used to guide future flood control measures. Finally, the study may be considered by other countries in their analysis of similar flooding experiences. Keywords: Barangay, Flood Risk, Assessment, Geographic Information System, Scenario
Keywords: Barangay, Flood Risk, Assessment, Geographic Information System, Scenario